2008
DOI: 10.1590/s1677-04202008000100005
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhiza influence on maize development under Cd stress and P supply

Abstract: The role of arbuscular mycorrhizal fungi (AMF) on cadmium (Cd) accumulation and on the possible attenuation of Cd stress was studied in maize plants (Zea mays L. var. Exceller). Plants inoculated or not with Glomus macrocarpum were exposed to Cd (0-20 µmol L -1 ), at two P levels (5 and 10 mg L -1 ) in the nutrient solution. The experiment was conducted in a hydroponic system, using a randomized 2 x 2 x 2 factorial design. The mycorrhiza-Cd interaction on plant growth, nutrients and Cd accumulation, AMF root c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 42 publications
(40 reference statements)
2
21
0
1
Order By: Relevance
“…Similar to this, a reduction in the colonizing ability of G. mosseae with increase in the HM concentration in soil has also been reported earlier by Citterio et al (2005) and Marques et al (2008). However, an efficient symbiosis capable of alleviating Cd stress was detected in our study, which is comparable to the results of Andrade and Silveira (2008), who also reported that Cd addition decreased the AM root colonization of plants and the development of intraradical mycelium besides alleviating Cd stress. Moreover, chelate toxicity was also noticed on addition of EDTA against G. mosseae, as AM spore number and AM colonization were reduced.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to this, a reduction in the colonizing ability of G. mosseae with increase in the HM concentration in soil has also been reported earlier by Citterio et al (2005) and Marques et al (2008). However, an efficient symbiosis capable of alleviating Cd stress was detected in our study, which is comparable to the results of Andrade and Silveira (2008), who also reported that Cd addition decreased the AM root colonization of plants and the development of intraradical mycelium besides alleviating Cd stress. Moreover, chelate toxicity was also noticed on addition of EDTA against G. mosseae, as AM spore number and AM colonization were reduced.…”
Section: Discussionsupporting
confidence: 92%
“…Plants possess different tolerance mechanisms to the high levels of Pb and other HMs in soils; among them, the association with the symbiotic arbuscular mycorrhizal (AM) fungi may confer tolerance to more sensitive species due to the increase in the absorption and utilisation of phosphorus (P) by mycorrhizal (M) plants (Chen et al 2005;Andrade and Silveira 2008;Soares and Siqueira 2008). An interesting feature of AM association is that it can increase or decrease the absorption capability of HMs by the plant (Ma et al 2006;Andrade et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, alguns fatores influenciam as associações micorrízicas, como a textura do solo; a calagem (Carrelho et al, 2007); o sistema de cultivo (Dawo et al, 2009); a contaminação do solo com metais pesados (Andrade & Silveira, 2008); as queimadas realizadas para a colheita de cana-de-açúcar (Reis et al, 1999); e os agrotóxicos, a exemplo dos herbicidas (Abd-Alla et al, 2000;Santos et al, 2006;Vieira et al, 2007), com respostas variadas em função do composto químico e da espécie de planta em questão (Bethlenfalvay et al, 1996).…”
Section: Introductionunclassified